Handbook of research on Web 2.0 and second language learning - Thomas, Michael, 1969- (Hershey, PA : Information Science Reference, 2009)
'This book investigates how those involved in education can respond to the opportunities offered by the Web 2.0 technology'--Provided by publisher
Includes bibliographical references (p. 546-596) and index
Keywords: Language and languages -- Computer-assisted instruction; Second language acquisition -- Computer-assisted instruction; Internet in education